Художественный перевод в обучении иностранным языкам: Межвуз. сб. / Чуваш. гос. ун-т им. И.Н.Ульянова - Иванов В. А. (1985)
Экземпляры: ИН (19981203) / Инвентарный номер: ин35164 / Цена: 1.00 / Сис.шифр: 81.2-9 / Авт.знак: Х 98 / ГРНТИ: 16 / ББК: 81.2-9